Audio Visual-Based Breaststroke Swimming Training Model for Beginner Athletes Elementary School (12-13 Years Old) - Suharmawan Ramadhan; Ramdan Pelana; Hernawan; Sulthan Hadist Ismaiedh Cukarso (Journal of Physical Education Health and Sport, 2026)
Breaststroke is one of the basic swimming styles most often learned by beginner athletes, but mastering the technique requires complex coordination between arm, leg and breathing movements. Innovation of audio-visual based training model is seen as a solution to increase the effectiveness of breaststroke technique learning. This study aims to develop and test the effectiveness of an audio-visual based breaststroke swimming training model for beginner athletes of elementary school (12–13 years old). This study uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 66 athletes divided into experimental and control groups. Data collection was carried out through observation, interviews, and swimming skills tests. Data analysis used descriptive statistics, normality tests, homogeneity tests, paired sample t-tests, and N-Gain tests with the help of IBM SPSS Statistics 25. The results showed that the developed training model was declared valid by material experts and media experts with several revisions for improvement. The implementation of the model showed a significant increase in the experimental group (t = -10.566; p < 0.05) compared to the control group (t = -8.527; p < 0.05). Improved learning outcomes in the experimental group demonstrated that integrating audiovisual media and ground training strengthened athletes' mental representations and motor coordination. The developed model not only improved performance but also enhanced the quality of the learning process in a more interactive and systematic way.